Hypothesis: Etiologic and Molecular Mechanistic Leads for Sporadic Neurodegenerative Diseases Based on Experience With Western Pacific ALS/PDC - Spencer, Peter S. (Frontiers in Neurology, 2019)
Seventy years of research on Western Pacific amyotrophic lateral sclerosis and Parkinsonism-dementia Complex (ALS/PDC) have provided invaluable data on the etiology, molecular pathogenesis and latency of this disappearing, largely environmental neurodegenerative disease. ALS/PDC is linked to genotoxic chemicals (notably methylazoxymethanol, MAM) derived from seed of the cycad plant (Cycas spp.) that were used as a traditional food and/or medicine in all three disease-affected Western Pacific populations. MAM, nitrosamines and hydrazines generate methyl free radicals that damage DNA (in the form of O6-methylguanine lesions) that can induce mutations in cycling cells and degenerative changes in post-mitotic cells, notably neurons. This paper explores exposures to naturally occurring and manmade sources of nitrosamines and hydrazines in association with sporadic forms of ALS (with or without frontotemporal degeneration), progressive supranuclear palsy, and Alzheimer disease. Research approaches are suggested to examine whether these associations might have etiological significance. Lay Summary Unknown environmental exposures are thought to be risk factors for non-inherited forms of certain progressive brain diseases, such as sporadic forms of amyotrophic lateral sclerosis (sALS), progressive supranuclear palsy (sPSP), and Alzheimer's disease (sAD). Related progressive and fatal brain disorders coalesce in a single neurodegenerative disease of largely environmental origin (ALS-Parkinsonism-dementia Complex) that has affected three genetically distinct populations residing in islands of the Western Pacific region. Prolonged study of this prototypical neurodegenerative disease has provided invaluable information on the probable environmental cause (specific chemical genotoxins) and molecular mechanisms (unrepaired nerve cell DNA-damage) by which brain degeneration begins, evolves and, years or decades later, clinical signs appear, and progress. This information is used as a foundation to explore whether chemically related genotoxins (nitrosamines, hydrazines) are possible risk factors for sALS, sPSP, and sAD. Methods to test this hypothesis in the field and laboratory are proposed.